Automated Large-Scale Full Seismic Waveform Inversion for North America and the North Atlantic - Krischer, Lion; Fichtner, Andreas; Boehm, Christian; Igel, Heiner (Journal of Geophysical Research: Solid Earth, 2018)
ISSN:2169-9313 ISSN:0148-0227 ISSN:2169-9356